MO019AURORA PHASE 3 TRIAL DEMONSTRATES VOCLOSPORIN STATISTICAL SUPERIORITY OVER STANDARD OF CARE IN LUPUS NEPHRITIS (LN). (6th June 2020) - Caster, Dawn J; Solomons, Neil; Randhawa, Simrat; Huizinga, Robert B
Abstract: Background and Aims: Voclosporin (VCS) is a novel high potency calcineurin inhibitor (CNI) with a favorable metabolic profile and a consistent predictable dose response potentially eliminating the need for therapeutic drug monitoring. The Aurinia Renal Response in Active Lupus with Voclosporin (AURORA) study, involving 357 patients with active LN, was a Phase 3 global, double-blind, placebo-controlled RCT designed to evaluate the efficacy and safety of VCS (23.7mg BID) vs placebo in combination with mycophenolate (MMF, 2 g/day) and rapidly tapered low dose oral steroids. Method: The primary endpoint was renal response (RR) at 52 weeks. RR was defined as UPCR of ≤ 0.5 mg/mg, eGFR ≥ 60 mL/min, or no confirmed decrease from baseline in eGFR of > 20%, presence of sustained, low dose steroids and no administration of rescue medication. Results: AURORA met its primary endpoint, achieving statistically superior RR rates of 40.8% for voclosporin vs. 22.5% for the control (OR 2.65, 95% CI; p < 0.001). The benefits of VCS were also seen for all predetermined secondary endpoints, achieving statistical significance in favor of VCS for RR at 24 weeks, partial renal response (PRR) at 24 and 52 weeks, time to achieve UPCR ≤ 0.5, and time to 50% reduction in UPCR. Prespecified confirmed eGFR decreases >30% were similar in both groups, with 10.1% reported in the VCS group and 10.2% in the control arm (p= 0.971). No significant differences were seen at any timepoints in the study. Furthermore, all pre-specified subgroup analyses (age, sex, race, biopsy class, region, and prior MMF use) also favored VCS. VCS was well tolerated with no unexpected safety signals. Similar SAEs were reported in the VCS group (20.8%) and in the control arm (21.3%). Infection was the most commonly reported SAE with 10.1% of VCS patients versus 11.2% of patients in the control arm. Overall mortality in the trial was low, with 6 deaths observed; 1 in the VCS arm and 5 in the control group. Additionally, the VCS arm showed no significant decrease at week 52 in eGFR or increase in BP, lipids or glucose. Conclusion: While maintaining a comparable safety profile, VCS plus standard therapy achieved a statistically superior RR over one year compared to placebo plus standard therapy in adults with active LN.